Efforts to Improve Down Passing Capability through Teaching Learning Styles 1 Perhhenian Raja Private School - Syahputra, Ardiyan; Apriani, Leni (JOURNAL RESPECS (Research Physical Education and Sports), 2024)
The aim of this research is to see the increase in down passing ability in volleyball games through the reciprocal teaching style method in class XI students at SMA Negeri 1 Perhentian Raja. Based on the results of observations of lower class passing. Many students are still careless when passing down. The teacher's teaching style is less effective so students feel bored. The test used in this research uses PTK which presents a two-cycle assessment rubric regarding down passes in volleyball. The research subjects in this study were 35 class XI students of SMA Negeri 1 Perhentian Raja. From the results found in the field, it is known that in cycle I it was found that 19 people or 54.28% had passed the KKM and there were 16 people or 45.71% who had not passed the KKM, while in cycle II it was found that 16 people or 45.71% had have not passed the KKM. that those who had passed the KKM were 30 people or 85.71% and those who had not passed the KKM were 5 people or 14.28%.